Kajian Tingkat Degradasi dan Depresiasi Sumberdaya Ikan Layaran (Istiophorus platypterus) menggunakan Model Bioekonomi Clarke Yoshimoto Pooley di Perairan Utara Aceh - Agus Naufal; Eka Purnama Sari; Faisal Syahputra; Mukhlis Mukhlis; Azwar Thaib; Teuku Faizul Anhar (Jurnal TILAPIA, 2023)
This study aims to assess the level of degradation and depreciation of the Layaran fishery in the North Coast of Aceh. The method used in this research includes stock assessment using the Clarke Yoshimoto Pooley (CYP) Bioeconomic model to assessing the degradation and depreciation that has occurred in the Layaran fishery. The estimated production value of the Maximum Sustainable Yield (MSY) is 4.63 tonnes per year which is greater than the actual production value of 3.33 tonnes per year and the MSY effort value is 36,642 trips per year which is greater than the actual effort 16,972 trips per year show that there has not been overfishing in the Layaran fishery, both in terms of production and fishing effort. Sailfish fisheries during the period 2009 to 2017 were also still in a non-degraded and depreciated condition as indicated by the coefficient values of the Degradation and Depreciation rates which were lower than the standard coefficient values with each value of 0.32 for the Degradation rate and 0.26 for the Depreciation rate.